2000
DOI: 10.1128/aem.66.6.2548-2554.2000
|View full text |Cite
|
Sign up to set email alerts
|

Surface of Lactic Acid Bacteria: Relationships between Chemical Composition and Physicochemical Properties

Abstract: The surface chemical composition and physicochemical properties (hydrophobicity and zeta potential) of two lactic acid bacteria, Lactococcus lactis subsp. lactis bv. diacetilactis and Lactobacillus helveticus, have been investigated using cells harvested in exponential or stationary growth phase. The surface composition determined by X-ray photoelectron spectroscopy (XPS) was converted into a molecular composition in terms of proteins, polysaccharides, and hydrocarbonlike compounds. The concentration of the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
145
3
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 203 publications
(166 citation statements)
references
References 55 publications
(76 reference statements)
15
145
3
3
Order By: Relevance
“…Il a été proposé d'expliquer les propriétés adhésives des bactéries par les propriétés physicochimiques globales de la surface des cellules [4]. Il a été établi que la surface lactococcale se compose principalement de protéines et de polysaccharides, et possède un caractère hydrophile [3]. Le rôle exact de chaque composant moléculaire de la surface des lactocoques dans l'adhésion et la formation d'un biofilm n'a pas encore été clairement établi.…”
Section: Attachement Aux Surfacesunclassified
“…Il a été proposé d'expliquer les propriétés adhésives des bactéries par les propriétés physicochimiques globales de la surface des cellules [4]. Il a été établi que la surface lactococcale se compose principalement de protéines et de polysaccharides, et possède un caractère hydrophile [3]. Le rôle exact de chaque composant moléculaire de la surface des lactocoques dans l'adhésion et la formation d'un biofilm n'a pas encore été clairement établi.…”
Section: Attachement Aux Surfacesunclassified
“…Chemical compounds present in food and pharmaceutical mixtures may influence interactions with surfaces and adhesion processes (Speranza et al, 2004). Proteins at the outer surface of bacteria are known to play an important role in the initial attachment to solid surfaces in water (Dufrêne et al, 1996;Flint et al, 1997;Caccavo, 1999;Boonaert and Rouxhet, 2000;Lower et al, 2005;Mercier-Bonin et al, 2009). In a work devoted to soiling by starch suspension, it was reported (Detry et al, 2011) that the presence of macromolecules, mainly polysaccharides, which were adsorbed from the liquid phase or carried by the retracting water film and deposited at the granulesubstrate interface, acted as an adhesive joint, the properties of which seemed to be influenced by the detailed history of drying and subsequent exposure to humidity.…”
Section: Introductionmentioning
confidence: 99%
“…Bruinsma et al (2001) observed that Pseudomonas aeruginosa grown to mid-exponential phase possessed greater concentrations of nitrogen-rich cell surface components and adhered better to hydrophobic and hydrophilic substrata than cells in the early stationary growth phase. Boonaert and Rouxhet (2000) reported that Lactobacillus helveticus contained more polysaccharide-rich compounds in stationary phase than during exponential growth. In contrast, other research indicated that bacterial surface compositions remain unchanged in response to growth phase.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Mozes et al (1988) showed that there was a direct correlation between the cell surface N:P atomic concentration ratio and the cell's electrostatic charge; the presence of phosphate groups mainly determined the anionic surface charges, while nitrogenous groups were linked to increased positive charges. Boonaert and Rouxhet (2000) suggested that the difference in electrokinetic properties between Lactococcus lactis and Lactobacillus helveticus is related to N:P surface concentration ratios, which reflects the relative exposure of proteins and phosphate groups at the surface. However, there is still a scarcity of information linking the alteration of N:P ratios to changes in bacteria cell wall composition or surface properties.…”
Section: Introductionmentioning
confidence: 99%